RELATIONSHIP BETWEEN DARK TRIAD PERSONALITY AND SELF-ESTEEM AMONG SPORTS PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
The Dark Triad consists of three personality traits: Narcissism, Psychopathy, and Machiavellianism. These traits have been linked to various negative behaviors and outcomes in interpersonal relationships and organizational settings. Investigate how the Dark Triad traits influence selected self-esteem variables in athletes participating in sports. The goal of this study is to look at the link between the Dark Triad and self-esteem among sports players who competed in inter-collegiate tournaments organized by Manonmaniam Sundaranar University in Tirunelveli, Tamil Nadu, India, during the academic year 2023-24. In this study, a sample of 50 athletes from several sports disciplines were assessed for Dark Triad and self-esteem. The participants were given two scales: the brief dark trait version, which measured the dark qualities, and the Self-Esteem Scale (1998), which measured their self-esteem. The study found a moderate positive association (r = 0.32, p < 0.01) between the Dark Triad and self-esteem ratings. Machiavellianism and psychopathy were the most significant variables contributing to the first canonical root in the dark personality set. Furthermore, accomplishment and reputation at work are valued. In the dark personality set, narcissism and psychopathy were associated with the second canonical root. While creativity and accomplishment were inversely connected with Machiavellianism and psychopathy, narcissism was favorably related to self-esteem